DOI: 10.11606/t.3.2019.tde-18072019-153134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticulate copper, zirconia and graphite: contribution to the friction coefficient and transfer layer formation in dry sliding tests with interfacial media addition.

Abstract: Copper is present in brake pads in the form of fibres, tough its suppression from pads' formulations is already a trend compared to the suppression of asbestos in the 1980's.As a contribution to this challenging scenario, this work investigated the behaviour of mixture additions containing copper, zirconia, graphite and magnetite in dry sliding tribotests. Pin-on-disc tribotests with interfacial media addition were performed in order to contribute on the mission of understanding how Cu, graphite and ZrO2 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Previous investigations [13,14] -using PoD tribotests under air atmosphere at room temperature and Fe 3 O 4 -Cu artificial third body -showed that copper promoted rougher sliding and CoF increase. Still, at 400 °C, copper promoted smoother sliding and lower CoF values [13][14][15]. Investigations [14,15] using PoD tribotests under air atmosphere at room temperature and Fe 3 O 4 -graphite artificial third body indicated that graphite causes a smoother sliding and reduces the CoF.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous investigations [13,14] -using PoD tribotests under air atmosphere at room temperature and Fe 3 O 4 -Cu artificial third body -showed that copper promoted rougher sliding and CoF increase. Still, at 400 °C, copper promoted smoother sliding and lower CoF values [13][14][15]. Investigations [14,15] using PoD tribotests under air atmosphere at room temperature and Fe 3 O 4 -graphite artificial third body indicated that graphite causes a smoother sliding and reduces the CoF.…”
Section: Introductionmentioning
confidence: 95%
“…Still, at 400 °C, copper promoted smoother sliding and lower CoF values [13][14][15]. Investigations [14,15] using PoD tribotests under air atmosphere at room temperature and Fe 3 O 4 -graphite artificial third body indicated that graphite causes a smoother sliding and reduces the CoF. Still, the graphite's effect on the CoF depends on the tribotest conditions, such as temperature, mixing mode, and atmosphere [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations